Students’ attitudes toward euthanasia and abortion: a cross-cultural study in three Mediterranean countries - Ivana Tutić Grokša; Ana Depope; Tijana Trako Poljak; Igor Eterović; Toni Buterin; Robert Doričić; Mariana Gensabella; Maria Laura Giacobello; Josip Guć; Eleni Kalokairinou; Željko Kaluđerović; Iva Rinčić; et al. (BMC Medical Ethics)
Abstract Introduction Abortion and euthanasia are still one of the greatest bioethical challenges. Previous studies have shown that there are differences in attitudes towards these issues depending on socio-demographic characteristics and socio-cultural environment (country of residence). As part of the scientific research project EuroBioMed, we compared the attitudes of students from three Mediterranean countries towards abortion and euthanasia and examined them from the perspective of Mediterranean bioethics. Methods A pen-to-paper survey was conducted on a convenient sample of students (N = 1097) from five universities and four fields of study (Medicine, Law, Theology and Philosophy) in Croatia, Greece and Italy to investigate their attitudes towards abortion and euthanasia. Three hypotheses were tested using t-test and ANOVA for differences in attitudes according to country, field of study, year of study, gender, religiosity, political orientation, financial status, and size of place of residence. Results While attitudes towards abortion were not statistically significantly different between students from different countries, the analysis showed that students from Italy had more liberal attitudes towards euthanasia. Theology students had more conservative attitudes towards both abortion and euthanasia, while there were no differences between the other groups. Women, final year students, non-religious and politically left-oriented students had more liberal attitudes. Conclusion The results provided an insight into students’ attitudes towards abortion and euthanasia. Knowledge of the attitudes of these future experts can be valuable for the discussion of these issues. These results also provided a basis for a better understanding of the construct of Mediterranean bioethics.